2016
DOI: 10.1186/s13584-016-0096-1
|View full text |Cite
|
Sign up to set email alerts
|

Trends in annual drug expenditure – a 16 year perspective of a public healthcare maintenance organization

Abstract: BackgroundModern drug therapy accounts for a major share of health expenditure and challenges public provider resources. The objective of our study was to compare drug expenditure trends for ten major drug classes over 16 years at Maccabi Healthcare Services (MHS), the 2nd largest healthcare organization in Israel.MethodsA retrospective analysis of drug expenditure per HMO beneficiary between the years 1998–2014. Trends in annual mean drug expenditures per MHS member were compared among 10 major drug classes.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Medicare must then, by law, provide any technologies that has FDA approval, thus weakening the ability to negotiate with pharmaceutical companies in order to lower costs. Furthermore, Lomnicky et al [ 4 ] found that even when a health plan is widely implementing cost containment methods its expenditure on cancer care technologies rises significantly over time.…”
Section: The Insurability Of Innovative Pharmaceutical Cancer Technolmentioning
confidence: 99%
See 2 more Smart Citations
“…Medicare must then, by law, provide any technologies that has FDA approval, thus weakening the ability to negotiate with pharmaceutical companies in order to lower costs. Furthermore, Lomnicky et al [ 4 ] found that even when a health plan is widely implementing cost containment methods its expenditure on cancer care technologies rises significantly over time.…”
Section: The Insurability Of Innovative Pharmaceutical Cancer Technolmentioning
confidence: 99%
“…Over the years, the number of drugs in Israel with a price of over NIS 10,000 per package has grown significantly, as has the average price of drugs [ 3 ]. Lomnicky et al [ 4 ] compared the trends in drug expenditure by the Maccabi Health Services over a 16-year period and found that while cancer drugs accounted for only 6.8% of its total drug expenditure in 1998, their proportion rose steadily over time to 30.2% in 2014, making them Maccabi’s largest single drug class expenditure. They explain this increase as being due to the increasing number of approvals for high-priced biological and targeted cancer therapies (such as monoclonal antibodies and modern tyrosine kinase inhibitors).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The topics covered include: the national initiative to increase health care equity [3], the pediatric dental reform [4], medical education [5, 6], advanced practice providers [7], tobacco control [8], and growing pharmaceutical expenses [9, 10]. In addition, since our last editorial [11] (December 2014), the IJHPR has published its first article by a Nobel Prize laureate [12], and its first contributions from China [13] and India [14].…”
mentioning
confidence: 99%
“…The first such symposium will be on the growing expenditures on cancer medications and the program will include presentations by authors of the relevant IJHPR articles [9, 10, 16, 17], along with presentations from Israeli health care leaders who are grappling with this issue.…”
mentioning
confidence: 99%